The Effect of ESG Score on Profit Informality: Analysis of Future Earnings Response Coefficient on the MSCI Indonesia Index - Rahmaningrum, Winda Ryzka Aulia; Purba, Marudut Rizky Martin; Qadri, Resi Ariyasa (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
The purpose of this study is to predict and explain the influence of ESG score on profit information proxied using  the Future Earnings Response Coefficient (FERC) approach in companies that are members of the MSCI Indonesia Index using a mix method approach. Quantitative data were obtained from annual reports, sustainability reports, and stock price data during the observation period, which were analyzed using FERC-based panel data regression models. Furthermore, a qualitative approach is used to interpret empirical results through the analysis of investor behavior, market characteristics, and the quality of ESG disclosures. The results of the study show that ESG scores did not have a significant effect on profit informability which is reflected in the market response to future profits, and is supported by qualitative findings that show that ESG has informational value for investors in the formation of stock prices. In practical terms, these results confirm the importance of increasing ESG score disclosure as a strategy to increase credibility and market perception.